“Voice of Student” in the Analysis of Components of Digital Educational Environment during Online Learning - Olga I. Popova; Galina S. Timokhina; Natalya B. Izakova; Larisa M. Kapustina (Интеграция образования)
Introduction. The importance of consumer experience research in online learning is determined by the competition of universities for consumers in the educational market. Existing studies in this problematic field are devoted to assessing students’ perception of only some aspects of online learning, which do not fully reflect the complexity of such a complex category as the “digital educational environment”. Based on the authors’ Voice of Student research algorithm, the aim of the study was to analyze students’ evaluations of the consumer’s experience of interaction with components of the digital learning environment during online learning.